Beyond access to medication: the role of SUS and the characteristics of HIV care in Brazil - Ana Maroso Alves; Angélica Carreira dos Santos; Aline Kumow; Ana Paula Sayuri Sato; Ernani Tiaraju de Santa Helena; Maria Ines Battistella Nemes (Revista de Saúde Pública, 2023)
ABSTRACT OBJECTIVE To estimate the public-private composition of HIV care in Brazil and the organizational profile of the extensive network of public healthcare facilities. METHODS Data from the Qualiaids-BR Cohort were used, which gathers data from national systems of clinical and laboratory information on people aged 15 years or older with the first dispensation of antiretroviral therapy between 2015–2018, and information from SUS healthcare facilities for clinical-laboratory follow-up of HIV, produced by the Qualiaids survey. The follow-up system was defined by the number of viral load tests requested by any SUS healthcare facility: follow-up in the private system – no record; follow-up at SUS – two or more records; undefined follow-up – one record. SUS healthcare facilities were characterized as outpatient clinics, primary care and prison system, according to the respondents’ self-classification in the Qualiaids survey (72.9%); for non-respondents (27.1%) the classification was based on the terms present in the names of the healthcare facilities. RESULTS During the period, 238,599 people aged 15 years or older started antiretroviral therapy in Brazil, of which 69% were followed-up at SUS, 21.7% in the private system and 9.3% had an undefined system. Among those followed-up at SUS, 93.4% received care in outpatient clinics, 5% in primary care facilities and 1% in the prison system. CONCLUSION In Brazil, antiretroviral treatment is provided exclusively by SUS, which is also responsible for clinical and laboratory follow-up for most people in outpatient clinics. The study was only possible because SUS maintains records and public information about HIV care. There is no data available for the private system.